Across the sub-Artics of Canada, a journey of 1,200 miles by canoe and snow-shoe through the barren lands - Tyrrell, James Williams, 1863-1945.; Heming, Arthur, 1871-1940. ill (New York, Dodd, 1898)
Mode of access: Internet.